(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
This article describes the combustion process of diesel fuel in terms of two main parameters - cetane number (determining engine power and economic indicators) and fractional composition (determining the completeness of fuel combustion, engine smoke and exhaust toxicity).